Análise numérica da resposta de implantes odontológicos com abutment de liga superelástica - Luiz Felipe Cardoso Lehman (2006)
Excessive loads over dental implants can cause marginal crest decrease through bone reabsoption or collapse of the components of the bone-implant system. The transmission reduction of the masticatory impacts to the bone adjacent to the dental implant is a challenge in the development of new materials for this application. Through simulationswith finite element analysis, the stresses produced by loads on the alveolar bone can be studied. This work had the goal to make a non-linear analysis of an abutment model, made of a superelastic alloy, for an implant using ANSYS version 9.0, and simulate the effect of the masticatory loads. Particularly, this study discuss loads transmission to the implant and consequently to the surrounding bone, aiming at evaluate the energy absorption by the material. Energy dissipation on the implant can work like a security system, helping to avoid the collapse of the components and diminishing the marginal crestal bone losses. Dynamic studies must be due to analyze the cyclic behavior of the NiTi under masticatory impacts.